Psoriasis Beyond Local Skin Disease (Medico Legal Update, 2021)
Background: Psoriasis is a skin disease that was associated with metabolic and clinical changes whichsuggest that psoriasis is a systemic rather than local disease.Aim: To illustrate whether psoriasis is local or systemic disease through analysis of some biomarkers.Materials and Method: A 256 subjects with psoriasis and 221 sex and age matched controls were includedin the study. Serum total cholesterol [TC], high density lipoprotein [HDL], Malondialdehyde [MDA],triglycerides [TG], and total antioxidant capacity [TCA] were determined using commercial kits.Results: There were no significant differences between psoriasis and control groups in regards to meanage and gender distribution, however, there was a significant difference [p